Change of students' problem-solving appraisal in higher education according to gender - Alci, Bulent; Canca, Deniz (ELSEVIER SCIENCE BV, 2011)
The purpose of this study is determining the effect of university education on students' problem-solving appraisal, including its difference according to gender. For this aim, 130 students were tested in the beginning and at the end of their undergraduate years. Findings reveal that while there is no significant difference in students' problem-solving appraisal points between their 1st and 4th years for the whole group and for the females, there is a significant positive difference for the males. This may be a result of the theory based instruction, variation of experiences, and differences in cognitive, physical, and social development. (c) 2011 Published by Elsevier Ltd.
Keywords: Problem-solving; appraisal; undergraduate; education; gender; SELF; Education & Educational Research